Transverse Stokes flow through regular arrays of cylinders - Zachara, A. (Archives of Mechanics, 1999)
The paper presents results of calculations of the Stokes flow trough square and triangular arrays of parallel cylinders. The results were derived using the method of singular force distributions [1]. The results are obtained to O(f7) for a square and to O(f8) for a triangular array, where f is the reduced volume fraction. They are compared with the results of previous authors. The new expressions for the drag force and the permeability coefficient valid in the whole range of f are also derived, using Padé approximation technique.